Intracyclic velocity variation and arm coordination assessment in swimmers with down syndrome - Marques-Aleixo, I.; Querido, A.; Figueiredo, P.; Vilas-Boas, J. P.; Corredeira, R.; Daly, D.; Fernandes, R. J. (Adapted Physical Activity Quarterly, 2013)
This study examined the differences in intracycle velocity variation and arm coordination in front crawl in swimmers with Down syndrome in three breathing conditions. International swimmers with Down syndrome (N = 16) performed 3 × 20 m front crawl at 50 m race speed: without breathing, breathing to the preferred side, and breathing to the nonpreferred side. A two dimensional video movement analysis was performed using the APASystem. Breathing conditions were com- pared using Repeated Measures ANOVA. Swimming velocity was higher without breathing and intracyclic velocity variation was higher while breathing. Swimmers tended to a catch up arm coordination mode for both breathing conditions and a superposition mode when not breathing. These data reflect arm coordination compromising swimming performance, particularly when comparing with non disabled swimmers in literature. The physical and perhaps cognitive impairment associated with Down syndrome may result in a disadvantage in both propulsion and drag, more evident when breathing.